If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 48) = 180 Reorder the terms: x + (48 + x) = 180 Remove parenthesis around (48 + x) x + 48 + x = 180 Reorder the terms: 48 + x + x = 180 Combine like terms: x + x = 2x 48 + 2x = 180 Solving 48 + 2x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 2x = 180 + -48 Combine like terms: 48 + -48 = 0 0 + 2x = 180 + -48 2x = 180 + -48 Combine like terms: 180 + -48 = 132 2x = 132 Divide each side by '2'. x = 66 Simplifying x = 66
| (-7x-3)(6x+7)+28x+12=0 | | Y=4x+6+7+26x | | ln(0,99)=-x/5 | | -10n+4=-20-12n | | 2x+3=5x+33 | | 10x-5=3-2x | | 2log=-3 | | 9/27=n/9n | | 9/27=n/9n= | | xdy+dyx=0 | | X-8.1=4.1 | | (4x-1)(5x+8)=0 | | X^2+10x=-28 | | 3x+9=4+36 | | 2X^2+9Y^2=25 | | 3.6/1.5 | | 3e^3x-12e^2x=0 | | 63=x+17-19 | | y^2-4y+43=0 | | (-9x-3)(-6x-6)-27x-9=0 | | 50x+6=20 | | 14r^8/2r^15 | | 3(y+7)=4(y-4) | | 3g+3=g+7 | | 333N/3 | | 2b=b-5 | | 2tanx/(sec^2x-2tan^2x)=tan2x | | 6g-g+8=3y | | 2a+12=6a | | 13a+4b+7a-b-2a= | | (2x+1)(x-1)=90 | | (2tanx)/(sec^2x-2tan^2x) |